Convergences and influences of discourses in an online professional development course for mathematics teachers - Erixon, Eva-Lena (NOMAD Nordic Studies in Mathematics Education, 2017)
Despite the ever-increasing number of online professional development (OPD) courses, few studies have examined online education for mathematics teachers. This article reports on a case study of discourses in an OPD course for mathematics teachers concerning the convergence and influence of discourses in course seminar discussions and in mathematics teaching in school when course participants are given the task of translating their insights into actual teaching, with a focus on the participants’ discussions of their own and one another’s video-recorded lessons. The analy- sis shows that there is a convergence of discourses in the seminars and in the school context related to a focus on concepts and everyday life connections. However, the study also suggests that there is a risk of students remaining outside in an ”everyday discourse”, in which knowledge of mathematics might be useful, but mathematics is discussed in imprecise and simplified terms.